Summer habitat use of plateau pikas (Ochotona curzoniae) in response to winter livestock grazing in the alpine steppe Qinghai-Tibetan Plateau - Badingquiying; Andrew T. Smith; Richard B. Harris (Arctic, Antarctic, and Alpine Research, 2018)
Plateau pikas (Ochotona curzoniae), burrowing lagomorphs endemic to the Qinghai-Tibetan Plateau (QTP), are considered pests by Chinese authorities because of their association with grasslands that are characterized as degraded. Officials typically blame pikas for causing the degraded conditions, whereas studies increasingly suggest that sparse vegetation encourages population growth and high densities of pikas. Correlational investigations that document pika density while simultaneously describing grassland conditions can quantify this association, but are uninformative regarding causation. We used livestock exclosures and pika reductions in partially controlled experiments to examine how pika habitat use responds to changes in vegetation structure caused by wintertime livestock grazing. Mean counts of pikas were higher on grazed than ungrazed plots. Linear models accounting for experimental pika reduction as well as seasonal phenology indicated that grazing significantly increased pika use compared with ungrazed plots. These results show that moderate livestock density is likely consistent with both biodiversity conservation and economic activity, and that high pika populations alone are not responsible for observed degradation of the QTP alpine grasslands. Moderate levels of livestock grazing and pika presence are consistent with maintaining the integrity of the alpine steppe ecosystem of the QTP.